Faktor-Faktor Yang Memengaruhi Nilai Perusahaan Dengan Risiko Kredit Sebagai Pemoderasi - Andry Priharta; Nur Asni Gani; Darto Darto; Sulhendri Sulhendri; Uun Uniyawati (Owner : Riset dan Jurnal Akuntansi, 2023)
The price that investors are prepared to pay for a business's stock is a good indicator of the firm's value, and hence the stock market price is a good indicator of the value of the company. The CGPI, ROA, NIM, and NPL are just a few examples of parameters that will be investigated in order to ascertain the degree to which they have an impact on PBV. In this line of investigation, we make use of the common effect model in conjunction with the panel data regression technique. The research sample is State-Owned Banks in Indonesia, specifically Bank Negara Indonesia (BBNI), Bank Rakyat Indonesia (BBRI), Bank Tabungan Negara (BBTN) and Bank Mandiri (BMRI). The period from 2011 to 2020 will be examined by the research. According to the findings, CGPI, ROA, and NIM each have a considerable influence on PBV that is both positive and beneficial. It has been established that the variable NPL moderates by lowering the influence that CGPI has on PBV. On the other hand, it has not been demonstrated that the variables ROA and NIM moderate. This is because the NPL number, despite having increased, is still regarded to be within the tolerance limit, making it an acceptable risk despite the fact that it has increased.